Developing EFL Junior Secondary School Students’ Narrative Writing Skill Using Brain Writing Model - Hardianti, Andi Emy; Baa, Sultan (Institut Agama Islam Negeri Palopo, 2025)
This research aimed to analyze: (1) the effectiveness of using the brain writing model in improving students' narrative writing skills. (2) EFL students’ perceptions on the use of brain writing model in improving their narrative writing skill. The method employed was quantitative, using a pre-experimental design consisting of a one-group pretest and posttest design. This research was conducted at SMPIT Al-Fatih Makassar academic year 2022/2023. The sampling technique used was random sampling with 18 students. Writing tests and questionnaires were utilized as research instruments. The data were analyzed using SPSS v.26. The findings revealed that brain writing model was effective in improving students' skill to write narrative texts. It was shown by the score of pre-test and post-test increased by 49%. The mean of pre-test score was 53.67, whereas the mean post-test score was 80.06. Next, N-Gain score from pre-test and post-test was 0.5632 and it was categorized as medium effective. Furthermore, the T value was 0.000 < 0.05 which mean significant. On the other side, post-test scores of students' narrative writing outcomes concluded that around 72% of students passed the minimum completeness criteria and 28% did not pass it. Besides, the other findings indicated that students showed positive perceptions related to benefits, interests, activities, and implementation on the use of brain writing model in improving narrative writing skill.